La difusión de contenidos falsos por parte de la fan page “El mercioco – sátira política” período enero – junio 2019 - Andrés Sebastián, Villarreal Panchi (2021)
ABSTRACT The current project called "THE DISSEMINATION OF FALSE CONTENT BY THE FAN PAGE "EL MERCIOCO – SÁTIRA POLÍTICA" PERIOD JANUARY - JUNE 2019", was carried out in order to know why false content is disseminated on social networks, also for knowing what the most vulnerable target in these cases is. Currently, cyberspace is an excellent help to people. However, it has a good and bad side. In applying the methodology, the scientific, inductive, and deductive methods were used; the type of research used is documentary, field research, analytical - descriptive. On the other hand, the research design is qualitative and quantitative since matrices, surveys, and interviews were carried out. Through the application of the matrices, the great reception that the publications on this site have was evidenced due to the reactions, comments, and times shared and the time for which they were published. In addition, the surveys conducted determined that people know how to differentiate fake news. Additionally, the interview served to deepen this topic where the main character is the network user. Finally, false content abounds in social networks, and most people have enough knowledge to differentiate fake news. It was concluded that baby boomers are the most vulnerable people; in this case, it is recommended to use the manual of good use of Facebook to generate a digital education in people and thus have good management of networks. Keywords: Fake news, followers, digital education, Facebook Reviewed by: Mgs. Hugo Romero ENGLISH PROFESSOR c.c. 0603156258